2005
DOI: 10.1152/ajpregu.00246.2004
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous system and blood pressure regulation in RGS2-deficient mice

Abstract: . Autonomic nervous system and blood pressure regulation in RGS2-deficient mice. Am J Physiol Regul Integr Comp Physiol 288: R1134-R1142, 2005. First published January 20, 2005; doi:10.1152/ajpregu.00246.2004.-Regulator of G protein signaling (RGS2) deletion in mice prolongs signaling by G protein-coupled vasoconstrictor receptors and increases blood pressure. However, the exact mechanism of the increase in blood pressure is unknown. To address this question we tested autonomic nervous system function and bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 40 publications
(52 reference statements)
4
78
0
Order By: Relevance
“…Targeted deletion of RGS2 in mice leads to a hypertensive phenotype, presumably due to prolonged G q/11 signaling and vasoconstriction in the vasculature (51,52). Central nervous mechanisms (an enhanced sympathetic tone that could lead to a resetting of the baroreceptor reflex) appear to also contribute to blood pressure elevation in this model (53). To date, very little is known about the cardiac phenotype of RGS2KO.…”
Section: Feasibility and Significance Of Rnai In Cardiac Myocytesmentioning
confidence: 90%
“…Targeted deletion of RGS2 in mice leads to a hypertensive phenotype, presumably due to prolonged G q/11 signaling and vasoconstriction in the vasculature (51,52). Central nervous mechanisms (an enhanced sympathetic tone that could lead to a resetting of the baroreceptor reflex) appear to also contribute to blood pressure elevation in this model (53). To date, very little is known about the cardiac phenotype of RGS2KO.…”
Section: Feasibility and Significance Of Rnai In Cardiac Myocytesmentioning
confidence: 90%
“…After recovery for 15 days, data were recorded under baseline conditions. Autonomic nerve activity was assessed by monitoring spontaneous changes in blood pressure and heart rate as described earlier (41).…”
Section: Methodsmentioning
confidence: 99%
“…8A). These observations raise the possibility that the three human RGS2 SNPs might negatively affect RGS2 mRNA expression, which might be expected to predispose to hypertension by analogy with effects of reduced RGS2 expression on blood pressure in genetically modified mice (3)(4)(5)(6)(7).…”
Section: Snps Identified In Human Hypertensive Patients Are Located Imentioning
confidence: 99%
“…RGS2 is expressed ubiquitously, and its major biological function is to serve as a GTPase-activating protein that preferentially attenuates heterotrimeric G protein G␣ q/11 GTPase activity (2). Several independent studies have demonstrated that Rgs2 knock-out mice have severe hypertension (3)(4)(5)(6)(7), suggesting that RGS2 plays a critical role in blood pressure homeostasis. Interestingly, heterozygous Rgs2 knockout mice are also hypertensive, and their blood pressures are virtually identical to homozygous Rgs2 knock-out mice (3), indicating that two functional Rgs2 alleles are required for normal blood pressure homeostasis.…”
mentioning
confidence: 99%